Časná diagnostika revmatoidní artritidy: Klíč k úspěšné terapii - Lukáč, Adam (Vnitřní lékařství, 2024)
Early diagnosis of rheumatoid arthritis (RA) is a key factor for successful treatment and improving patient prognosis. This article provides an overview of the diagnostic approach for RA. It also discusses the challenges associated with early diagnosis. Furthermore, it focuses on the benefits of early treatment initiation, including reducing disease progression and improving patients' quality of life. In conclusion, recommendations for clinical practice are provided, emphasizing the importance of timely recognition and intervention in patients with RA. This article highlights the necessity of a proactive approach by physicians to early RA diagnosis and supports further research in the diagnosis and treatment of this condition. Understanding diagnostic procedures and the benefits of early RA treatment can contribute to improving clinical practice and outcomes for patients with this disease.
Keywords: stupeň závažnosti nemoci; Early Diagnosis; antiflogistika; časná diagnóza; Methotrexate; Ambulatory Care Facilities; lidé; Arthritis, Rheumatoid; ambulantní zařízení; Severity of Illness Index; revmatoidní artritida; methotrexát; Anti-Inflammatory Agents; Humans